Desain dan Implementasi Aplikasi Kasir Rental Mobil Menggunakan Visual Studio - Bhramantyo, Achileus Danatha; Shafara, Amanda Haikal; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
This study presents an analysis of the development of a Visual Studio-based Car Rental application that aims to simplify the online car rental process. By increasing the need for more efficient transportation solutions, the app is designed to overcome obstacles in car rental, such as distance and information limitations. The methods used in this study include interviews with users and service providers, observation of existing rental practices, and literature related to information technology. The development results show that this application has a simple and user-friendly interface, is able to manage customer and vehicle data in a structured manner, and improves operational efficiency for service providers. In conclusion, the Car Rental application not only provides convenience for users but also supports the growth of the car rental business in the digital era.